PENGGUNAAN MEDIA STORY PHOTO PADA PEMBELAJARAN SAKUBUN I BERDASARKAN JAPAN FOUNDATION STANDARD CAN-DO A1 (Studi Terhadap Mahasiswa Tingkat I Pendidikan Bahasa Jepang Universitas Riau) - Inayah, Evi; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study describes and explains the application of Story Photo media in Sakubun I Learning Based on the Japan Foundation Standard Can-Do A1 in the Japanese language education students of FKIP Riau University. The purpose of this study was to determine empirically the presence or absence of the influence of the use of Story Photo media on the first sakubun learning based on JF Standard Can-do A1 and to find out whether there were significant differences in the learning outcomes of Level I students after using Story Photo media in Sakubun learning. In this study the authors used weak experimental or weak experiments. This study did not use a comparison group, so it was only carried out in the same class. The test results were processed using SPSS Version 16. The test results in the pretest and posttest of the experimental class had increased, the average pretest score of students was 10.42 while the posttest was 18.39. Thus, the Essay Photo media is effective in improving the learning outcomes of 2018 FKIP Japanese language education students.Key Words: Photo Essay Media, Japan Foundation Standard, Can-Do A1